Analisis Tingkat Pendapatan Pedagang Kaki Lima Di Kawasan Wisata Lembah Indah Kecamatan Ngajum Kabupaten Malang - Lisa Yunita (Jurnal Ilmu Ekonomi, 2021)
This study aims to determine how much the income of street vendors in Lembah Indah Tourist area, Ngajum District, Malang Regency and How the influence t of capital, length of business, and working hours on the income of street vendors in Lembah Indah Tourist area, Ngajum District, Malang Regency. The data used in this study are primary data obtained using field research sourced from street vendors in the Lembah Indah tourist area as a sample. The data were analyzed using descriptive qualitative and quantitative descriptive analysis methods with data collection techniques through an open questionnaire. The samples taken were all traders, amounting to 25 respondents using census techniques. The analysis tool uses SPSS, including normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, t-test, F test, and determinant coefficient. This study indicates that the variables of initial capital, length of business, and working hours have a significant effect on income.